Impact of solid waste on water quality: a case study of Gokarna landfill site, Kathmandu - Devkota, Dinesh C.; Watanabe, Kunio; Dangol, Vishnu (Journal of Nepal Geological Society, 2004)
The Gokarna landfill site (GLS) was in operation between 1986 and 1996. At present, there is a high risk of shallow aquifer contamination owing to the absence of a barrier layer and a high rate of leachate in now from the landfill site. About 20 m thick sandy bed is transmitting pollutants to the shallow aquifer. The water quality analysis of shallow wells, dug wells and springs around the GLS carried out between November 2003 and March 2004 revealed that they are polluted by the leachate. The heavy metal concentration, chlorides, iron as well as BOD and COD values depicted their increasing trend. Likewise, the microbial contamination was also high, and the water was unsuitable for domestic use. However, there is a low probability of contaminating the deep aquifer owing to the presence of impermeable layers of silt and clay above it. On the other hand, the amount of pollutants in the leachate has decreased significantly in recent years, especially after 1996.